Kleinian singularities and algebras generated by elements that have given spectra and satisfy a scalar sum relation - Mellit, A. (Algebra and Discrete Mathematics, 2004)
We consider the algebras eiΠλ (Q)ei , where Πλ (Q) is the deformed preprojective algebra of weight λ and i is some vertex of Q, in the case where Q is an extended Dynkin diagram and λ lies on the hyperplane orthogonal to the minimal positive imaginary root δ. We prove that the center of eiΠλ (Q)ei is isomorphic to Oλ (Q), a deformation of the coordinate ring of the Kleinian singularity that corresponds to Q. We also find a minimal k for which a standard identity of degree k holds in eiΠλ (Q)ei . We prove that the algebras AP₁,...,Pn;µ = Chx₁, . . . , xn|Pi(xi) = 0, Pn i=1 x₁ = µei make a special case of the algebras ecΠλ (Q)ec for star-like quivers Q with the origin c.